In vitro and in vivo activity of essential oils against postharvest pathogen Colletotrichum musae of banana - Kumar, Deepak; Arya, Santosh K; Shamim, Md; Srivastava, Deepti; Tyagi, Manjusha; Singh, K N (Journal of Postharvest Technology, 2021)
Anthracnose caused by Colletotrichum musae is a serious postharvest disease of immature and mature fruit of banana. The synthetic fungicides are used to control this disease but in current scenario, fungicides prohibited in many countries that reduce their commercial value. Therefore, presented study was conducted to evaluate the antifungal activity in vitro and in vivo for find out alternative products to the synthetic fungicides. Two different approaches were used; poisoned food technique was used for in vitro studies while pre-inoculated banana fruits with phytopathogen (C. musae) and essentials oils’ treatments in vivo conditions. The results indicated that all essential oils inhibited the mycelial growth of pathogen over untreated PDA plates. Schleichera oleosa oil was superior among all treatments in vitro against pathogen C. musae, it was twofold higher to rest other EOs. Similarly, under in vivo conditions, all essential oils showed significant influence on lesion diameter, decay incidence, decay loss, physiological loss in weight and storage life but Schleichera oleosa oil was the most effective. The storage life of banana fruits was higher in Schleichera oleosa oil (25% v/v) treated fruits (viz 4.5 days more) compared to untreated and rest EOs treated banana fruits after 15 days of storage under ambient conditions (22±20C, 72-75% RH). Thus presented studies revealed that unexploited essential oils have the potential to control anthracnose disease without causing harmful effects on banana fruits, and can be recommended as safe biofungicides for extending storage life and quality attributes.